2020
DOI: 10.1136/openhrt-2020-001343
|View full text |Cite
|
Sign up to set email alerts
|

Real-world evaluation of perception, convenience and anticoagulant treatment satisfaction of patients with atrial fibrillation switched from long-term vitamin K antagonist treatment to dabigatran

Abstract: Background and purposeReal-world data about treatment convenience and satisfaction in Asian non-valvular atrial fibrillation (NVAF) patients after switching from vitamin K antagonists (VKAs) to non-VKA oral anticoagulants were evaluated.MethodsIn this non-interventional study involving 49 sites across five countries in Southeast Asia and South Korea, 379 stable NVAF patients who switched from VKA therapy to dabigatran during routine clinical practice were recruited and followed up for 6 months. Treatment conve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…It may be that in the PREFER in AF registry substudy, complaints about bruising/bleeding, treatment dissatisfaction and anxiety/depression may have influenced the switching from VKAs to NOACs. Multiple studies published subsequently have consistently observed that the NOACs, in comparison with the VKAs, have higher treatment satisfaction, convenience and perceived benefits, and lower perceived disease and treatment burdens in patients suffering from NVAF18 19 24 30–32 and also from other conditions where the NOACs are indicated 33 34. Consistent with recent studies, our study also shows higher treatment convenience and satisfaction scores with dabigatran compared with VKAs and adds to a growing wealth of data.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…It may be that in the PREFER in AF registry substudy, complaints about bruising/bleeding, treatment dissatisfaction and anxiety/depression may have influenced the switching from VKAs to NOACs. Multiple studies published subsequently have consistently observed that the NOACs, in comparison with the VKAs, have higher treatment satisfaction, convenience and perceived benefits, and lower perceived disease and treatment burdens in patients suffering from NVAF18 19 24 30–32 and also from other conditions where the NOACs are indicated 33 34. Consistent with recent studies, our study also shows higher treatment convenience and satisfaction scores with dabigatran compared with VKAs and adds to a growing wealth of data.…”
Section: Discussionsupporting
confidence: 90%
“…17 Higher scores in PACT-Q2 indicate better convenience and higher treatment satisfaction 16. Two recent studies, one conducted in Europe and Israel and the other in South East Asia and South Korea, showed significant improvements in treatment convenience and satisfaction scores in patients who switched from a VKA to dabigatran for stroke prevention 18 19. In this study, PACT Q2 was used to evaluate patient perception of anticoagulation with dabigatran versus VKAs when used for stroke prevention in patients with newly diagnosed AF in South East Asia and South Korea.…”
Section: Introductionmentioning
confidence: 99%
“…Reasons for high levels of compliance with DOACs likely include ease of use, including no requirement to monitor DOAC levels except for special cases such as in patients with particularly high or low body weight. 30–33 The advantage of lack of necessity to monitor anticoagulation with DOACs may improve patients' access to treatment (eg, for those in remote rural areas). DOAC plasma levels also decrease quickly, 33 allowing more straightforward surgical interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Patients' preferences are critical in determining adherence to OAC. In a recent study from Asia, the substitution of VKA therapy with dabigatran was associated with a significant improvement in treatment convenience and satisfaction [95], suggesting that NOACs are favored by AF patients themselves. Patients' sociodemographic characteristics and physicians' level of experience with VKAs vs. NOACs are other factors that could be relevant in choosing the type of OAC [18].…”
Section: Additional Evidence That May Reinforce the Choice Of Using Non-vitamin K Antagonists Instead Of Vitamin K Antagonistsmentioning
confidence: 99%